Production Ethics Research Trend a Bibliometric Analysis - Sholahuddin, Muhammad; Nilam Saputri , Iin (Universitas Muhammadiyah Surakarta, 2023)
This study presents a novel exploration of the research trends in Sharia Production Ethics, focusing on publications from leading journals in the field. By employing bibliometric analysis, this quantitative study provides valuable insights into the development of this area of study. The dataset analyzed comprises 337 Scopus-indexed research publications spanning the years 1993 to 2022. The data underwent rigorous processing and analysis using bibliometric R applications (bibliophily R) and VOS viewers. The findings of this study shed light on the notable growth in the number of publications dedicated to Sharia Production Ethics. Notably, journal articles emerge as the primary document type for analyzing this field. Among the authors in this domain, Hughes and Holloway stand out for their significant contributions, as evidenced by the number of documents they have authored. Furthermore, this study identifies key thematic areas within the research on Sharia Production Ethics, as reflected by the most frequently used keywords. These keywords encompass a broad range of topics, including Co-Production, Knowledge Production, Research, Ethics, Sustainability, Policy, Agriculture, Climate Change, Methodology, Regulation, Ethical Consumption, and Technology. By covering these diverse aspects of Production Ethics within Islamic economics, this study provides both informative and complementary insights. Its contribution lies in offering a comprehensive overview of the research landscape in Sharia Production Ethics, highlighting the increasing interest in this field and identifying key researchers and thematic areas.